Early Life Nutrition. (October 2018) - Finn, Susan; Culligan, Eamonn P.; Snelling, William J.; Sleator, Roy D.
Nutritionally, the first 1, 000 days of an infant's life – from conception to two years – has been identified as a highly influential period, during which lasting health can be achieved. Significant evidence links patterns of infant feeding to both short and long-term health outcomes, many of which can be prevented through nutritional modifications. Recommended globally, breastfeeding is recognised as the gold standard of infant nutrition; providing key nutrients to achieve optimal health, growth and development, and conferring immunologic protective effects against disease. Nevertheless, infant formulas are often the sole source of nutrition for many infants during the first stage of life. Producers of infant formula strive to supply high quality, healthy, safe alternatives to breast milk with a comparable balance of nutrients to human milk imitating its composition and functional performance measures. The concept of 'nutritional programming', and the theory that exposure to specific conditions, can predispose an individual's health status in later life has become an accepted dictum, and has sparked important nutritional research prospects. This review explores the impact of early life nutrition, specifically, how different feeding methods affect health outcomes.